Maternal Dietary Diversity and Infant Outcome of Pregnant Women in Northern Ghana - Saaka, Mahama (International Journal of Child Health and Nutrition, 2013)
Objective: Little is known regarding the role of maternal dietary diversity score (DDS) in predicting poor outcomes of pregnancy including preterm delivery, and low birth weight (LBW). The main aim of this study was to explore the relationship between dietary diversity scores of urban Ghanaian women and infant weight at birth. Methods: This analytical cross-sectional study comprised 524 pregnant women who delivered singleton babies. A Structured questionnaire was used to collect data on socio-demographic variables (e.g. educational status, age, maternal occupation, household wealth index), obstetric history (for example, gravidity, gestational weight gain), dietary intake, malarial infection and Sulphadoxine pyrimethamine (SP) uptake, blood pressure (BP), haemoglobin concentration (Hb), anthropometric measurements (e.g. weight of mother and new born baby). Results: This study showed that maternal dietary diversity as measured by individual dietary diversity score scores (IDDS) was a significant independent predictor for mean birth weight and LBW. Analysis of covariance (ANCOVA) showed there was a significant difference in adjusted mean birth weight between women on low and high diversified diets , F (1, 415) = 8.935, p = 0.003. The results further showed that maternal IDDS was negatively associated with the incidence of LBW (Adjusted OR = 0.43, 95% CI = 0.22–0.85, p = 0.014). Conclusion: In nutritional deprived populations, maternal diet in the third trimester appears to be an important determinant of LBW and that DDS can serve as useful predictive indicator of maternal nutrition during pregnancy and the likelihood of delivering LBW babies.